I know this is good, but I am confused: English teachers self-efficacy in implementing the Independent Curriculum - Zuliati Rohmah; Hamamah Hamamah; Esti Junining (Studies in English Language and Education, 2024)
Several studies have been conducted to determine the implementation of the Independent Curriculum. However, the existing studies have not identified English teachers self-efficacy in implementing the curriculum. Therefore, the present research aims to investigate the English teachers self-efficacy in applying the Independent Curriculum in secondary schools in Indonesia. This study was a mixed method study using a questionnaire and focus group discussions with teachers in teacher support groups. The data was collected from 171 secondary school English teachers. The results show that most English teachers understand the freedom offered by the government to schools and teachers in the new curriculum. However, they have low self-efficacy in implementing the curriculum in the teaching-learning process. They do not have adequate knowledge of how to translate the learning objectives specified by the government into their own syllabi. They do not have sufficient understanding or ability to conduct a needs analysis and syllabus design as a prerequisite for implementing the curriculum. Our research suggests that the teachers need further support from the government and teacher trainers through in-person hands-on training and workshops on needs analysis, syllabus design, and materials selection and development to effectively implement the Independent Curriculum.